2022
DOI: 10.3389/fcvm.2022.867428
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urate in Cardiovascular Risk in Adolescents and Young Adults With Hypertension, Assessed by Pulse Wave Velocity

Abstract: BackgroundUrate is increasingly recognized as a cardiovascular risk factor. It has been associated with hypertension, metabolic syndrome, obesity, chronic kidney disease and diabetes. Its prognostic role is less clear. The aim of our study was to evaluate the association between serum urate and pulse wave velocity, a measure of arterial stiffness in hypertensive adolescents and young adults.Methods269 adolescents and young adults with hypertension were included in the study. From all, anthropometric, blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In a sample of 188 adolescents affected by type 1 diabetes, no association could be observed between arterial stiffness and SUA values, suggesting that SUA seems not to be associated with vascular abnormalities in this clinical setting (48). Accordingly, Mocnik et al (49) did not find any associations between SUA and arterial stiffness in a cohort of 269 hypertensive adolescents and young adults at increased risk for subclinical atherosclerosis. In the Lytvyn et al study (47), the lack of association between SUA and PWV might be due to the stimulatory effect of urinary glucose on the GLUT9 in the proximal tubule which increases uric acid excretion in diabetes (50).…”
Section: Discussionmentioning
confidence: 90%
“…In a sample of 188 adolescents affected by type 1 diabetes, no association could be observed between arterial stiffness and SUA values, suggesting that SUA seems not to be associated with vascular abnormalities in this clinical setting (48). Accordingly, Mocnik et al (49) did not find any associations between SUA and arterial stiffness in a cohort of 269 hypertensive adolescents and young adults at increased risk for subclinical atherosclerosis. In the Lytvyn et al study (47), the lack of association between SUA and PWV might be due to the stimulatory effect of urinary glucose on the GLUT9 in the proximal tubule which increases uric acid excretion in diabetes (50).…”
Section: Discussionmentioning
confidence: 90%
“…The reason for the gender difference in SUA between boys and girls during adolescence is that the SUA of boys increase sharply, while the SUA of girls remain relatively unchanged ( 26 ). Studies have shown that increased renal urate retention may be the main underlying mechanism of increased SUA ( 27 ). Adolescents have a progressive decline in renal fractional UA excretion and clearance, leading to increased UA retention ( 28 ).…”
Section: Discussionmentioning
confidence: 99%